Kajian Epigrafi pada Piagem Kesultanan Palembang - Fadhilah, Rohhimah Nur; Ngurah Tara Wiguna, I Gusti (Humanis, 2019)
Piag?m Kesultanan Palembang is one of the cultural heritage ini Rejang Lebong Regency, Bengkulu province. This inscription issued by one of the Kanjeng Sultan during administration Kesultanan Palembang Darussalam in 1729 ?aka (1807 AD). This study aims to describe the result of study on the inscription of Piag?m Kesultanan Palembang related to the aspects of language and social institutions contained in Piag?m Kesultanan Palembang . The data collection methods applied in this research were observation , interviews, and literature studies as well as data processing method through Countextual and qualitative analysis. The Theories that is use is structuralism theories.Based on the analysis results it could be seen that the paleography aspect Piag?m Kesultanan Palembang used the script of shift Javanese and language. The spelling used was the spelling which had evolved in the past. The affixation types used in this Piag?m Kesultanan Palembang were : prefix: ka- , in-, a- and Confix: a – k?n . The aspects of social institutions mentioned in Piag?m Kesultanan Palembang namely political institutions which included the central level bureacucracy in which the supreme power was held by the Sultan. Legal institutions is also found in Piag?m Kesultanan Palembang that mentioned about states debts and receivables regulation, tribute payment, trading, the law of theft, fine of murder, in the event of prisoners escaping, treasure discoveries, and the people who become the slave in the Abdi Da?m Kesultanan.